2022
DOI: 10.3389/fpsyg.2022.1016963
|View full text |Cite
|
Sign up to set email alerts
|

The first session is the one that counts: An exploratory study of therapeutic alliance

Abstract: BackgroundThe controversy about whether psychotherapy outcome is the consequence of the techniques themselves, common factors or both is still current. The importance of common factors has been demonstrated, although it is also known that they alone are insufficient. At the present time, the contextual model grants heavy weight to the therapeutic alliance in the first sessions and seems to predict positive final results. Furthermore, monitoring sessions has demonstrated that this alliance improves.ObjectivesTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The first sessions of therapy appear to be critical for both early response and therapeutic alliance building, regardless of treatment approach (Beard & Delgadillo, 2019; Fluckiger, Del Re, et al, 2020). Several studies across various therapeutic schools indicate that a strong initial therapeutic alliance correlates with enhanced early and long‐term treatment outcomes (Del Rio Olvera et al, 2022; Falkenström et al, 2013; Fluckiger, Del Re, et al, 2020; Kramer et al, 2009; Levy et al, 2015; Samstag et al, 2008; Wampold & Imel, 2015). Interestingly, a study on cognitive behavioural therapy for eating disorders revealed that early response was a more potent predictor of treatment outcome than the therapeutic alliance (Turner et al, 2015).…”
Section: Objectivementioning
confidence: 99%
“…The first sessions of therapy appear to be critical for both early response and therapeutic alliance building, regardless of treatment approach (Beard & Delgadillo, 2019; Fluckiger, Del Re, et al, 2020). Several studies across various therapeutic schools indicate that a strong initial therapeutic alliance correlates with enhanced early and long‐term treatment outcomes (Del Rio Olvera et al, 2022; Falkenström et al, 2013; Fluckiger, Del Re, et al, 2020; Kramer et al, 2009; Levy et al, 2015; Samstag et al, 2008; Wampold & Imel, 2015). Interestingly, a study on cognitive behavioural therapy for eating disorders revealed that early response was a more potent predictor of treatment outcome than the therapeutic alliance (Turner et al, 2015).…”
Section: Objectivementioning
confidence: 99%
“…In most psychotherapeutic endeavors, compassion and trust must be conveyed for clinical interventions to be maximally successful. The first moments of the first session may be exceptionally important ( 40 ). An example illustrating how even the smallest interaction may be important at this initial meeting involves how providers may best escort new patients from the waiting room to the treatment room after first greeting them.…”
Section: Interventions Likely To Be Optimalmentioning
confidence: 99%